2012
DOI: 10.1101/gad.182345.111
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a target cell permissive factor required for contact-dependent growth inhibition (CDI)

Abstract: Bacterial contact-dependent growth inhibition (CDI) is mediated by the CdiB/CdiA family of two-partner secretion proteins. CdiA effector proteins are exported onto the surface of CDI+ inhibitor cells, where they interact with susceptible bacteria and deliver effectors/toxins derived from their C-terminal regions (CdiA-CT). CDI+ cells also produce an immunity protein that binds the CdiA-CT and blocks its activity to prevent autoinhibition. Here, we show that the CdiA-CT from uropathogenic Escherichia coli strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
162
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(165 citation statements)
references
References 44 publications
3
162
0
Order By: Relevance
“…The critical role of EF-Ts in CdiA-CT EC869 toxicity appears to be similar to CdiA-CT EC536 , which only exhibits tRNA anticodon nuclease activity when bound to CysK (17,18). To determine whether EF-Ts activates CdiA-CT EC869 in the same manner, we tested CdiA-CT EC869 activity in defined in vitro reactions.…”
Section: Trna Cugmentioning
confidence: 99%
See 2 more Smart Citations
“…The critical role of EF-Ts in CdiA-CT EC869 toxicity appears to be similar to CdiA-CT EC536 , which only exhibits tRNA anticodon nuclease activity when bound to CysK (17,18). To determine whether EF-Ts activates CdiA-CT EC869 in the same manner, we tested CdiA-CT EC869 activity in defined in vitro reactions.…”
Section: Trna Cugmentioning
confidence: 99%
“…Most CDI nuclease domains efficiently cleave their substrates in vitro, but the CdiA-CT EC536 toxin deployed by uropathogenic E. coli 536 requires an additional factor to promote its tRNA anticodon nuclease activity (17). Using biochemical approaches, we discovered that the biosynthetic enzyme O-acetylserine sulfhydrylase A (CysK) binds the toxin with high affinity and stimulates its nuclease activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been demonstrated that deletion of genes belonging to the cysteine biosynthetic pathway leads to a bacterial phenotype with reduced virulence, compromised fitness and a susceptibility to antibiotics several fold higher than the wild strains 8,9 . The recent disclosure of a number of additional moonlighting activities of OASS, specifically for OASS-A isoform, that is, toxin activation in some strains of Escherichia coli (E. coli) 10 , gene expression in Bacillus subtilis (B. subtilis) 11 , and the involvement of the enzyme in some pathologically relevant processes as the formation of biofilm and swarming motility, has further focused the interest of researchers toward these proteins [11][12][13][14][15][16][17][18] . These activities span from toxin activation in contact-dependent growth inhibition of uropathogenic E. coli strains 10 , to gene expression in B. subtilis 11 and the involvement of the enzyme in some pathologically-relevant processes as the formation of biofilm and swarming motility 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The CdiA-CT EC536 region is composed of two domains that have distinct functions during CDI (9). The extreme C-terminal domain is an Ntox28 RNase family member (Pfam: PF15605) and is responsible for growth-inhibition activity (3,8). The N-terminal domain facilitates translocation of the tethered nuclease into the cytosol of target bacteria (9).…”
mentioning
confidence: 99%